Espectroscopía molecular útil en la determinación de biomarcadores de exposición y susceptibilidad (2021)
Spectroscopy is one of the tools most used in the analysis of different environmental sources, it allows to know the composition of organic and inorganic species, allowing studies in the area of health, detection of genotoxic substances, drug development, responses to treatment, among others. For decades molecular spectroscopy has made it possible to carry out quantitative and qualitative analyzes, by means of methods that reveal the properties, composition of materials, samples and simple or complex substances (molecules, ions, groups or metabolites), through the emission of radiation that said samples absorb, getting to know the composition of the matter characterizing it from spectra, images and numerical results. The following work aimed to collect information associated with molecular spectroscopy useful in determining biomarkers of exposure and susceptibility, thus revealing useful information for future research in Colombia. For this, a bibliographic compilation was carried out through the use of databases such as: Science Direct, Brazilian Journal of Pharmaceutical Sciences, Latin American Chemistry Journal, Medicine Journal, Sanitary Gazette Journal, among others. As a result of this research, bases were obtained for the orientation of research projects, analyzes, studies, types of biomarkers or alterations that may present in certain environmental spheres, health, drugs when exposed to external or toxic substances. The information to be reported will be from a reliable and updated source to obtain as a result a truthful study with current antecedents, the information to be shown was collected and verified through the use of software, which guarantees the veracity of said information, a description will be made, obtaining clear chapters with accurate information that respond to each specific objective raised in this final monograph report.